Particles having a specific low-order titanium oxide crystal composition and method for producing the same
Patent Information
- Application Number
- JP2022543926
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-21
- Filing Date
- 2021-08-13
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-08-13
Smart Images

Figure 0007634015000004 
Figure 0007634015000005 
Figure 0007634015000006
Abstract
Description
[Technical field]
[0001] This disclosure relates to Ti 2 O 3 and γ-Ti 3 O 5 The present invention relates to particles having the above crystal composition, and a method for producing the same. [Background technology]
[0002] It is known that low-order titanium oxide (also called reduced titanium oxide) obtained by reducing titanium dioxide exhibits different colors depending on the ratio of the constituent elements titanium and oxygen, and can become black by appropriately adjusting this ratio. Therefore, particles whose surfaces are composed of low-order titanium oxide can be used for various purposes as pigments such as black pigments. For example, Patent Document 1 discloses a cosmetic product using a pigment that exhibits dichroism, in which the appearance color and the interference color are different, by forming a single layer of low-order titanium oxide on a plate-like particle. In addition, Patent Document 2 discloses a cosmetic product using CaH as a reducing agent for applications such as black pigments. 2 Patent Document 3 discloses a black titanium oxide powder produced by reacting titanium oxide with high-temperature ammonia gas. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-280607 A [Patent Document 2] JP 2012-214348 A [Patent Document 3] JP 2010-30842 A Summary of the Invention [Problem to be solved by the invention]
[0004] Although black pigments containing low-order titanium oxide are generally called black, they can have different shades of black, such as a black with a strong reddish tinge or a black with a strong blue tinge. The shade of black can vary not only depending on the composition of low-order titanium oxide as described above, but also depending on the particle size of the pigment (particles). Therefore, in order to obtain a black pigment of a desired shade, it is possible to adjust physical properties such as particle size. However, such physical properties may be restricted by, for example, the application of the black pigment, so it is preferable to obtain a black pigment of a desired shade only by adjusting the composition of low-order titanium oxide.
[0005] Therefore, an object of one aspect of the present invention is to obtain particles of low-order titanium oxide having a novel composition. [Means for solving the problem]
[0006] The inventors have developed TiH 2 and TiO 2 When particles containing low-order titanium oxide are produced by heating, TiH 2 and TiO 2 It has been found that by appropriately adjusting the compounding ratio and the heating temperature, particles having a novel low-order titanium oxide composition can be obtained. 2 O 3 and γ-Ti 3 O 5 It has a crystal composition consisting of:
[0007] That is, one aspect of the present invention is a TiH 2 and TiO 2 The method further comprises a step of heating the mixture containing TiH 2 TiO 2 is 3.1 to 4.6. In this step, the mixture may be heated under an Ar gas atmosphere.
[0008] Another aspect of the present invention is a method for producing a Ti 2 O 3 and γ-Ti 3 O 5The crystal composition is Ti 2 O 3 γ-Ti 3 O 5 The particle has a molar ratio of L of 0.1 or more. * a * b * In color space, a * The value is 0 or more, and b * The particle may have a value of not more than 0. The total content of Na, K and P in the particle may be not more than 2000 ppm by mass.
[0009] Another aspect of the present invention is a dispersion containing the above-mentioned particles and a dispersion medium. Effect of the Invention
[0010] According to one aspect of the present invention, it is possible to obtain low-order titanium oxide particles having a novel composition, which makes it easy to adjust the black color of a dispersion containing the low-order titanium oxide particles (for example, a resin composition containing the low-order titanium oxide particles and a resin). [Brief description of the drawings]
[0011] [Figure 1] 1 shows the results of X-ray diffraction measurements in Examples and Comparative Examples. [Diagram 2] 1 shows the results of X-ray diffraction measurements in Examples and Comparative Examples. [Diagram 3] 1 shows the results of X-ray diffraction measurements in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] One embodiment of the present invention is a Ti 2 O 3 and γ-Ti 3 O 5 This method is a method for producing particles (hereinafter also referred to as "low-order titanium oxide particles") having a specific crystal composition (details will be described later) consisting of TiH 2 and TiO 2 The method further comprises a step of heating the mixture containing the above (heating step).
[0013] The mixture used in the heating step is, for example, powdered TiH 2 and powdered TiO 2 The mixture is not formed into pellets or the like (powdered TiH 2 and TiO 2 In the form of powder, TiH 2 and TiO 2 The properties of each can be appropriately selected. For example, powdered TiH 2 and TiO 2 The particle size of the TiH 2 and TiO 2 It may contain only TiH 2 , TiO 2 and unavoidable impurities. Examples of unavoidable impurities include Al. 2 O 3 , ZrO 2 , and C (carbon). TiH 2 and TiO 2 The total amount of may be 90% by weight or more, 95% by weight or more, or 99% by weight or more, based on the total amount of the mixture.
[0014] TiH contained in the mixture 2 TiO 2 Molar ratio of (TiO 2 Content (mol) / TiH 2 The content (mol) of is 3.1 to 4.6. If the molar ratio is less than 3.1, the amount of γ-Ti in the obtained particles may be large. 3 O 5 In this case, the low-order titanium oxide particles tend to be black-yellow in color. If the molar ratio exceeds 4.6, the resulting particles will not contain Ti. 2 O 3 In this case, the low-order titanium oxide particles tend to be black-blue in color.
[0015] The larger the molar ratio, the more γ-Ti in the obtained particles. 3 O5 The proportion of Ti 2 O 3 The proportion of is low. The lower limit of the molar ratio may be 3.2 or more, 3.3 or more, 3.4 or more, 3.5 or more, 3.6 or more, 3.7 or more, 3.8 or more, 3.9 or more, 4.0 or more, 4.1 or more, or 4.2 or more. The upper limit of the molar ratio may be 4.5 or less, 4.4 or less, 4.3 or less, 4.2 or less, 4.1 or less, 4.0 or less, 3.9 or less, 3.8 or less, 3.7 or less, 3.6 or less, or 3.5 or less.
[0016] In the heating step, the mixture is heated at 700 to 900° C., for example, in an electric furnace. This reduces the titanium dioxide, and the desired low-order titanium oxide (Ti 2 O 3 and γ-Ti 3 O 5 If the heating temperature is less than 700°C, the resulting particles will contain Ti. 2 O 3 and γ-Ti 3 O 5 is not generated, for example, Ti n O 2n-1 If the heating temperature exceeds 900°C, the resulting particles may contain γ-Ti 3 O 5 is not generated, for example, α-Ti 3 O 5 and β-Ti 3 O 5 may be generated.
[0017] The mixture is heated, for example, in an inert gas atmosphere. The inert gas is Ar gas or N 2 The titanium oxide particles may be a gas, which makes it easier to obtain low-order titanium oxide particles having a desired crystal composition (for example, TiO x From the viewpoint of further suppressing the generation of x≧1.75), Ar gas is preferred.
[0018] The heating time may be, for example, 1 hour or more, 2 hours or more, or 4 hours or more from the viewpoint of allowing the reduction reaction to proceed sufficiently, and may be, for example, 24 hours or less, 18 hours or less, or 12 hours or less from the viewpoint of appropriately suppressing the growth of the low-order titanium oxide particles and making them easy to collect in a powder state.
[0019] In one embodiment, this production method may further include a step of washing the low-order titanium oxide particles (washing step). Impurities can be removed by the washing step. The washing is carried out, for example, with at least one selected from the group consisting of hot water, alcohol, and organic acid. The alcohol may be, for example, methanol, ethanol, or a mixture thereof. The organic acid may be, for example, acetic acid. Washing with an organic acid is preferable from the viewpoint of suppressing the incorporation of ionic impurities such as halide ions into the low-order titanium oxide powder.
[0020] This production method preferably further includes a step of pulverizing the low-order titanium oxide particles after the heating step (pulverizing step). The pulverizing method in the pulverizing step may be a method using various pulverizers such as a mortar, a ball mill, a jet mill, a fine mill, etc. The pulverizing step may be performed once or may be performed two or more times. When the pulverizing step is performed two or more times, the pulverizing methods used in each pulverizing step may be different from each other. By performing the pulverizing step, the chromaticity and specific surface area of the low-order titanium oxide particles can be adjusted.
[0021] When this manufacturing method includes a washing step and a pulverization step, the order of these steps is arbitrary. That is, this manufacturing method may include a heating step, a washing step, and a pulverization step in this order, or may include a heating step, a pulverization step, and a washing step in this order. In the former case, a step of drying the low-order titanium oxide particles (drying step) may be further carried out between the washing step and the pulverization step. The drying temperature in the drying step may be, for example, 100° C. or higher and 200° C. or lower. The drying time may be, for example, 10 hours or higher and 20 hours or lower.
[0022] The low-order titanium oxide particles obtained by the above-described production method are 2 O 3 and γ-Ti 3 O 5 It has a crystal composition consisting of Ti 2 O 3 and γ-Ti 3 O 5 The crystal composition consisting essentially of Ti 2 O 3 and γ-Ti 3 O 5 This means that only low-order titanium oxide particles are included. 2 O 3 and γ-Ti 3 O 5 The crystal composition of the low-order titanium oxide particles is measured by X-ray diffraction (XRD) and is found to be substantially composed of Ti 2 O 3 and γ-Ti 3 O 5 This is confirmed by observing only the diffraction peaks due to each of the low-order titanium oxide particles. 2 O 3 and γ-Ti 3 O 5 The crystal phase may be a mixed phase of the above two types of crystal phases.
[0023] In the above crystal composition of the low-order titanium oxide particles, Ti 2 O 3 γ-Ti 3 O 5 Molar ratio of (γ-Ti 3 O 5 Content (mol) / Ti 2 O 3 The content (mol) of is 0.1 or more. The molar ratio may be 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, or 1.0 or more, and may be 50 or less, 40 or less, 30 or less, 25 or less, 20 or less, 15 or less, 10 or less, 8 or less, or 5 or less. The molar ratio is calculated by the following formula. Molar ratio (γ-Ti 3 O 5 / Ti 2 O 3 )=(M1 / F1) / (M2 / F2) In the formula, M1 is the γ-Ti in the low-order titanium oxide particles. 3 O 5 F1 is the mass fraction of γ-Ti 3 O 5 M2 represents the formula weight (=223.60) of Ti in the low-order titanium oxide particles. 2 O 3 F2 is the mass fraction of Ti 2 O 3 Represents the formula mass (=143.73).
[0024] γ-Ti in low-order titanium oxide particles 3 O 5 Mass fraction (M1) and Ti 2 O 3 The mass fraction (M2) of Ti is calculated by Rietveld analysis of the X-ray diffraction pattern. Specifically, Rietveld software (for example, Rigaku Corporation's integrated powder X-ray analysis software PDXL2) is used, and the crystal structure is calculated from the crystal structure database (Pearson's Crystal Data) using Ti. 2 O 3 1243140 (Journal of Applied Physics 119, 014905 (2016)), γ-Ti 3 O 5 The above mass fractions are calculated using the formula 1900755 (Journal of Solid State Chemistry 20, 29 (1977)) as the mass fraction.
[0025] The low-order titanium oxide particles have the above-mentioned crystal composition, and therefore exhibit a black color having a predetermined chromaticity. * a * b * L in color space * The L value of the low-order titanium oxide particles is preferably 13 or less, more preferably 11 or less, and even more preferably 10 or less, and may be, for example, 4 or more, 5 or more, or 6 or more. * a * b *a in color space * The L value of the low-order titanium oxide particles is preferably −1 or more, more preferably 0 or more, and is preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less. * a * b * b in color space * The value is preferably −8 or more, more preferably −6 or more, even more preferably −4 or more, and is preferably 1 or less, more preferably 0 or less.
[0026] L * a * b * L in color space * Value, a * value and b * The value is measured using a colorimeter (e.g., ZE-2000 (manufactured by Nippon Denshoku Industries Co., Ltd.)). More specifically, after zero-point correction using a dark field cylinder, standardization is performed using a standard white plate (X=91.71, Y=93.56, Z=110.52). Next, approximately 3 g of low-order titanium oxide particles are placed in a 35φ×15H round cell and measured.
[0027] The specific surface area of low-order titanium oxide particles is 0.25 m 2 / g or more, 1m 2 / g or more, 2m 2 / g or more, 3m 2 / g or more, or 4m 2 / g or more, 2 / g or less, 10m 2 / g or less, or 8m 2 The specific surface area of the low-order titanium oxide particles is measured using a specific surface area measuring device (e.g., Macsorb HM model-1201, manufactured by Mountech Co., Ltd.) under the conditions of degassing at 200°C for 10 minutes with nitrogen gas flow (atmospheric pressure), and nitrogen gas adsorption at an equilibrium relative pressure of about 0.3, n=2.
[0028] The amount of impurities in the low-order titanium oxide particles is preferably as small as possible. The content of Al in the low-order titanium oxide particles may be preferably 200 mass ppm or less, 50 mass ppm or less, or 20 mass ppm or less. The content of B in the low-order titanium oxide particles may be preferably 50 mass ppm or less, 30 mass ppm or less, or 10 mass ppm or less. The content of Ba in the low-order titanium oxide particles may be preferably 50 mass ppm or less, 10 mass ppm or less, or 5 mass ppm or less. The content of Ca in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 50 mass ppm or less, or 10 mass ppm or less. The content of Cd in the low-order titanium oxide particles may be preferably 10 mass ppm or less, 5 mass ppm or less, or 2 mass ppm or less. The content of Co in the low-order titanium oxide particles may be preferably 10 mass ppm or less, 5 mass ppm or less, or 2 mass ppm or less. The Cr content in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 10 mass ppm or less, or 5 mass ppm or less. The Cu content in the low-order titanium oxide particles may be preferably 200 mass ppm or less, 50 mass ppm or less, or 10 mass ppm or less. The Fe content in the low-order titanium oxide particles may be preferably 200 mass ppm or less, 50 mass ppm or less, or 10 mass ppm or less. The K content in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 5 mass ppm or less, or 1 mass ppm or less. The Li content in the low-order titanium oxide particles may be preferably 20 mass ppm or less, 2 mass ppm or less, or 0.5 mass ppm or less.
[0029] The content of Mg in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 10 mass ppm or less, or 1 mass ppm or less. The content of Mn in the low-order titanium oxide particles may be preferably 10 mass ppm or less, 5 mass ppm or less, or 2 mass ppm or less. The content of Mo in the low-order titanium oxide particles may be preferably 10 mass ppm or less, 5 mass ppm or less, or 2 mass ppm or less. The content of Na in the low-order titanium oxide particles may be preferably 50 mass ppm or less, 5 mass ppm or less, or 2 mass ppm or less. The content of Ni in the low-order titanium oxide particles may be preferably 50 mass ppm or less, 20 mass ppm or less, or 10 mass ppm or less. The content of P in the low-order titanium oxide particles may be preferably 200 mass ppm or less, 30 mass ppm or less, or 5 mass ppm or less. The content of Pb in the low-order titanium oxide particles may be preferably 50 mass ppm or less, 5 mass ppm or less, or 2 mass ppm or less. The content of Sb in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 10 mass ppm or less, or 2 mass ppm or less. The content of Si in the low-order titanium oxide particles may be preferably 1000 mass ppm or less, 100 mass ppm or less, 30 mass ppm or less, or 2 mass ppm or less. The content of Zn in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 10 mass ppm or less, or 2 mass ppm or less. The content of Zr in the low-order titanium oxide particles may be preferably 100 mass ppm or less, 20 mass ppm or less, or 2 mass ppm or less.
[0030] The total content of Na, K and P in the low-order titanium oxide particles may be preferably 2000 mass ppm or less, 1000 mass ppm or less, 500 mass ppm or less, or 100 mass ppm or less. The total content of Pb, Cd and Cr in the low-order titanium oxide particles may be preferably 200 mass ppm or less, 100 mass ppm or less, 50 mass ppm or less, or 30 mass ppm or less. The amount of impurities in the low-order titanium oxide particles is measured by elemental analysis (for example, Agilent 5110 ICP-OES (manufactured by Agilent Technologies, Inc.) is used.
[0031] The above-mentioned low-order titanium oxide particles are preferably used as a pigment (coloring filler) such as a black pigment. Such a pigment (coloring filler) is preferably used as a coloring agent, for example, in cosmetics, electronic components such as semiconductors, and coating materials such as paints and inks.
[0032] When the low-order titanium oxide particles are used for the above-mentioned applications, the low-order titanium oxide particles are used, for example, dispersed in a dispersion medium. That is, another embodiment of the present invention is a dispersion containing the low-order titanium oxide particles described above and a dispersion medium in which the low-order titanium oxide particles are dispersed.
[0033] The dispersion medium is appropriately selected depending on the application of the dispersion, and may be, for example, water, alcohol, ketone, ester, resin, etc. Examples of the resin may be, for example, epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamideimide, polyetherimide, polybutylene terephthalate, polyethylene terephthalate, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS (acrylonitrile-butadiene-styrene) resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc.
[0034] The content of the low-order titanium oxide particles in the dispersion is appropriately selected depending on the application of the dispersion, and may be, for example, 5% by mass or more and 90% by mass or less based on the total amount of the dispersion. The content of the dispersion medium in the dispersion is appropriately selected depending on the application of the dispersion, and may be, for example, 10% by mass or more and 95% by mass or less based on the total amount of the dispersion. EXAMPLES
[0035] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples.
[0036] <Preparation of low-order titanium oxide particles> [Example 1] TiO 2 10g of powder (Toho Titanium Co., Ltd. product, HT0514: purity 99.9%) and TiH 2 Powder (TOHO TECH, TCH450: purity 99.8%) 2.02 g (TiO 2 / TiH 2 =3.1 / 1 (molar ratio)) was mixed in an Eirich mixer (manufactured by Nippon Eirich Co., Ltd.) to obtain a mixture. This mixture was transferred to an alumina crucible and heated for 12 hours in an Ar atmosphere in an electric furnace (Fuji Dempa Kogyo Co., Ltd., Hi-Multi 5000) while increasing the temperature to 800°C at a rate of 10°C / min. After heating, the obtained powder was pulverized in a mortar for 5 minutes to obtain black low-order titanium oxide particles.
[0037] [Examples 2 to 9] TiH 2 TiO 2 Molar ratio of (TiO 2 / TiH 2 ) as shown in Table 1. 2 Black low-order titanium oxide particles were obtained in the same manner as in Example 1, except that the amount of the powder was changed.
[0038] [Example 10] Black low-order titanium oxide particles were obtained in the same manner as in Example 6, except that the heating time was changed to 4 hours.
[0039] [Examples 11 and 12] Except for changing the heating temperature as shown in Table 1, the same procedure as in Example 6 was carried out to obtain black low-order titanium oxide particles.
[0040] [Comparative Examples 1 and 2] TiH 2 TiO 2 Molar ratio of (TiO 2 / TiH 2 ) as shown in Table 1. 2 Particles were obtained in the same manner as in Example 1, except that the amount of powder was changed.
[0041] [Comparative Examples 3 and 4] Particles were obtained in the same manner as in Example 6, except that the heating temperature was changed as shown in Table 1.
[0042] [X-ray Diffraction Measurement] Powder X-ray diffraction measurements were performed on each of the particles of the above Examples and Comparative Examples. Specifically, a diffraction pattern was measured under the following measurement conditions using a sample horizontal multi-purpose X-ray diffractometer (manufactured by Rigaku Corporation, RINT-UltimaIV). The obtained X-ray diffraction patterns are shown in Figs. 1 to 3. (Measurement Conditions) X-ray source: Cu-Kα ray (λ = 1.54184 Å) Tube voltage: 40 kV, tube current: 40 mA Optical conditions during measurement: Divergence slit = 2 / 3° Scattering slit: 8 mm Receiving slit = 0.15 mm Position of diffraction peak = 2θ (diffraction angle) Scan speed: 4.0° (2θ) / min, continuous scan Measurement range: 2θ = 10° to 80°
[0043] Subsequently, the mass fractions (mass %) of Ti 2 O 3 and γ-Ti 3 O 5 in the obtained particles were calculated using Rietveld method software (manufactured by Rigaku Corporation, integrated powder X-ray analysis software PDXL2). The crystal structure was obtained from the crystal structure database (Pearson’s Crystal Data) as Ti 2 O 3 with 1243140 (Journal of Applied Physics 119, 014905 (2016)) and γ-Ti 3 O 5 with 1900755 (Journal of Solid State Chemistry 20, 29 (1977)) were used. Also, the mass fraction M1 of γ-Ti 3 O 5 and Ti 2 O3 Mass fraction M2 of γ-Ti 3 O 5 Formula mass F1 (=223.60) and Ti 2 O 3 From the formula F2 (=143.73), Ti 2 O 3 γ-Ti 3 O 5 Molar ratio of (γ-Ti 3 O 5 / Ti 2 O 3 ) into the following formula: Molar ratio (γ-Ti 3 O 5 / Ti 2 O 3 )=(M1 / F1) / (M2 / F2) The results are shown in Table 1.
[0044] <Chromaticity measurement> The chromaticity (L * a * b * L in color space * Value, a * value and b * The chromaticity was measured. More specifically, the zero point was first corrected using a dark field cylinder, and then standard alignment was performed using a standard white plate (X=91.71, Y=93.56, Z=110.52). Next, approximately 3 g of particles were placed in a 35φ×15H round cell, and the chromaticity was measured. The results are shown in Table 1.
[0045] <Measurement of specific surface area> The specific surface area of each particle in the above examples was measured using a specific surface area measuring device (Macsorb HM model-1201, manufactured by Mountech Co., Ltd.). Degassing was performed at 200°C for 10 minutes using nitrogen gas flow (atmospheric pressure). The measurement conditions were nitrogen gas adsorption with an equilibrium relative pressure of about 0.3 and n=2. The results are shown in Table 1.
[0046] [Table 1]
[0047] [Example 13] The black low-order titanium oxide particles obtained in Example 6 were pulverized using a single track jet mill Model FS-4 (manufactured by Seishin Enterprise Co., Ltd.) under the following pulverization conditions to obtain black low-order titanium oxide particles. (Crushing conditions) Pressure nozzle pressure (air pressure that pushes the raw materials into the grinding chamber) / Grinding nozzle pressure (air pressure that collides the raw materials together in the grinding chamber): 0.70MPa / 0.70MPa Processing capacity: 1.5kg / hr
[0048] [Examples 14 and 15] Using a fine mill SF15 (manufactured by Nippon Coke Corporation), the black low-order titanium oxide particles obtained in Example 6 were pulverized and classified under the following pulverization and classification conditions, and the black low-order titanium oxide particles were recovered using the cyclone and bag filter of the fine mill. The black low-order titanium oxide particles recovered using the cyclone were designated Example 14, and the black low-order titanium oxide particles recovered using the bag filter were designated Example 15. (Crushing and classification conditions) Ball: Zirconia (dimensions: φ5, usage: 30.6 kg) Agitator: Rotation speed: 440 min -1 , Classification rotor: Rotation speed: 8000 min -1 , Roots Blower: Frequency: 30.0Hz, Grinding aid: Ethanol (0.5 wt% of raw material)
[0049] The chromaticity and specific surface area were measured in the same manner as described above for each of the particles of Examples 13 to 15. The results are shown in Table 2.
[0050] [Table 2]
[0051] <Elemental analysis> For each particle of the above examples, elemental analysis was performed using Agilent 5110 ICP-OES (manufactured by Agilent Technologies, Inc.). Specifically, 0.1 g of particles was weighed into a platinum crucible, 1 ml each of HF and HCl was added, and pressure acid decomposition was performed at 150°C for 4 hours. Thereafter, the volume was adjusted to 6 ml, and after confirming that there was no unnecessary residue, ICP emission spectrometry was performed. The results are shown in Table 3. In Table 3, "ND" means that the value was below the lower limit of detection, and the value in parentheses means that the value was below the lower limit of quantification. The lower limit of detection and the lower limit of quantification are as follows. (detection limit) Li, Na, Mg, K and Ca: 0.5 ppm by mass P:5 mass ppm Elements other than the above: 2 ppm by mass (lower limit of quantitation) Li, Na, Mg, K and Ca: 2 ppm by mass P: 10 mass ppm Elements other than those mentioned above: 5 ppm by mass
[0052] [Table 3]
Claims
1. A method for producing low-order titanium oxide particles having a crystal composition consisting of Ti 2 O 3 and γ-Ti 3 O 5 , in which a molar ratio of said γ-Ti 3 O 5 to said Ti 2 O 3 is 0.1 or more, comprising the steps of: T.I.H. 2 and TiO 2 Heating the mixture at 700 to 900° C. The TiH contained in the mixture 2 The TiO 2 The molar ratio of is 3.1 to 4.
6.
2. The method according to claim 1 , wherein in the step, the mixture is heated in an Ar gas atmosphere.
3. Ti 2 O 3 and γ-Ti 3 O 5 having a crystal composition consisting of The Ti 2 O 3 The γ-Ti 3 O 5 The low-order titanium oxide particles have a molar ratio of 0.1 or more.
4. L * a * b * In color space, a * The value is 0 or more, and b * The low-order titanium oxide particles according to claim 3, wherein the value is 0 or less.
5. The low-order titanium oxide particles according to claim 3 or 4, wherein the total content of Na, K and P in the particles is 2000 ppm by mass or less.
6. A dispersion comprising the low-order titanium oxide particles according to any one of claims 3 to 5 and a dispersion medium.
Citation Information
Patent Citations
Fine powder of electroconductive titanium oxide of low oxidation state and its preparation
JP1986106414A
Production of color pigment
JP1989108125A
Production of high purity titanium suboxide
JP1989290529A
Production of lowly oxidized titanium-containing powder
JP1994321540A
Pigment, coating material, and method for producing them
JP2004231927A